2018
DOI: 10.2147/ott.s153375
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich alpha-2-glycoprotein-1 is up-regulated in colorectal cancer and is a tumor promoter

Abstract: BackgroundLeucine-rich α-2-glycoprotein-1 (LRG1) is differentially expressed in many kinds of diseases including cancer, however, it has not been thoroughly studied yet.PurposeThe objective of this study was to detect the expression and potential mechanism of LRG1 in colorectal cancer (CRC). In our study, we examined LRG1 levels in CRC tissue and plasma with quantitative real-time polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. The effect of LRG1 on cancer cells was detected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
8
27
2
Order By: Relevance
“…Since tumor progression is tightly associated with re-arrangement of the extracellular matrix, employment of AMBP, ITIH1, and ITIH4 may also support the net benefit for early detection of CRC and designation of probable cell migration. However, results of ITIH2 measurement contradict the previously reported data [47,48], which makes early recognition of CRC less confident and specific (Supplementary Materials Table S5).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Since tumor progression is tightly associated with re-arrangement of the extracellular matrix, employment of AMBP, ITIH1, and ITIH4 may also support the net benefit for early detection of CRC and designation of probable cell migration. However, results of ITIH2 measurement contradict the previously reported data [47,48], which makes early recognition of CRC less confident and specific (Supplementary Materials Table S5).…”
Section: Discussioncontrasting
confidence: 67%
“…Nevertheless, another family member, ITIH2, is typically exhausted or displays significant down-regulation in CRC pathology (up to 61% of tumor cases, [47]), which is at odds with the obtained results in our study on positive regulation of ITIH2 (FC = 2.18, Supplementary Materials Table S4). Previously, a strong link between the expression levels of ITIH2 and estrogen levels has been demonstrated, since ITIH2 contains an estrogen-binding domain which might be critical for metastasis and tumor growth because estrogen has a profound effect on extracellular matrix integrity [48]. However, due to the fact that our results do not completely agree with earlier established reports, we are reluctant to make a final conclusion in relation to ITIH2 levels in CRC patients.…”
Section: Relationship Between Inter-α-trypsin Inhibitor Heavy Chains contrasting
confidence: 73%
“…In addition, the protein is secreted and may therefore end up in blood or stool. Indeed, increased protein levels of LRG1 in plasma have been reported for colorectal cancer and colon adenoma patients [40,43,44]. Altogether, for the majority of these biomarker proteins their potential involvement in tumor biology has been demonstrated.…”
Section: Discussionmentioning
confidence: 98%
“…Then it was found to increase in response to mediators of acute phase response [4] and promote angiogenesis [7]. Thus LRG level was elevated in inflammatory diseases [12] and some cancers [13][14][15]. Recent study also found elevation of LRG is associated with arterial stiffness, endothelial dysfunction, peripheral vascular disease and CAD [16][17][18].…”
Section: Discussionmentioning
confidence: 99%